2014
DOI: 10.2527/jas.2013-7402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary humic and butyric acid on growth performance and response to lipopolysaccharide in young pigs1

Abstract: Humic acid (MFG) and fat-protected butyric acid (BA) has been shown to modulate energy metabolism and inflammation. Therefore, the objectives of this study were to determine the effects of MFG and BA, alone and in combination, on growth performance and response to lipopolysaccharide (LPS)-induced inflammation in young pigs. An experiment was conducted using 448 crossbred weanling pigs, which were stratified by gender and BW and were randomly assigned to 1 of 4 dietary treatments in a 2 × 2 factorial arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
3
11
0
2
Order By: Relevance
“…However, HS are substances with very complex structures and it cannot be expected that two separate sources of HS will contain identical molecules and exert the same effects on the animal or human body (Vaskova et al 2011). Weber et al (2014) suggested that HS in the diet of young pigs (0.25% for 35 days) may play a role in negating the effects of oxidative stress within the body. The inclusion of HS in the diets of broilers and growing pigs was found to reduce lipid peroxidation in muscle tissues during storage which had a positive effect on meat quality (Aksu et al 2005;Bai et al 2013).…”
Section: Biomarker Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HS are substances with very complex structures and it cannot be expected that two separate sources of HS will contain identical molecules and exert the same effects on the animal or human body (Vaskova et al 2011). Weber et al (2014) suggested that HS in the diet of young pigs (0.25% for 35 days) may play a role in negating the effects of oxidative stress within the body. The inclusion of HS in the diets of broilers and growing pigs was found to reduce lipid peroxidation in muscle tissues during storage which had a positive effect on meat quality (Aksu et al 2005;Bai et al 2013).…”
Section: Biomarker Of Oxidative Stressmentioning
confidence: 99%
“…In some reports, it was remarked that HS may have the potential to negate the effect of oxidative stress within the body (Ipek et al 2008;Weber et al 2014). On the other hand, HS, specifically HA, administered over a long period at high levels has been reported to induce damage in cells and tissues accompanied by an increase in oxidative stress and lipid peroxidation (Cheng et al 1999;Varanka et al 1999;Gau et al 2001;Ho et al 2003;Qi et al 2008).…”
mentioning
confidence: 99%
“…До таких речовин належать сполуки гумінової природи, які проявляють імуномодулюючий, адаптогенний, антистресовий, гепатопротекторний і ензимостимулюючий ефект на живі системи. Висока екологічна безпека гумінових речовин, які складають основу витяжок з торфу та унікальна здатність покращувати обмінні процеси, підвищувати енергетику клітин та проявляти антиоксидантні властивості ефективна при будь-яких відхиленнях, які відбуваються в організмі, сприяючи відновленню фізіологічних функцій при патологічних станах і в екстремальних ситуаціях [7,8,9].…”
Section: Buchko_oksana@ukrnetunclassified
“…З іншої сторони, гумати здатні до хелатоутворення, а саме можуть утворювати стійку сполуку з мікроелементами, покращувати їх засвоєння з раціону і цим позитивно впливати на активність і синтез ензимів та метаболітів САЗ організму. В наших дослідженнях це зростання активності СОД та КАТ, до активного центру яких входять Цинк, Купрум і Ферум, ГПз Селеном в активному центрі [9,12]. Інтенсифікацією енергетичних та посиленням процесів фосфорилювання [8] за впливу Гуміліду можна пояснити зростання концентрації ВГ та активності ГР, яка відновлює останній з окисленої форми в присутності НАДФH.…”
Section: Buchko_oksana@ukrnetunclassified
“…38,39 Many studies have reported that the humate can block the production of stress causing hormones, improve the immune system, has antibacterial and antifungal properties, liver effect, detoxifier properties. [40][41][42][43][44] Therefore, humate contributes to human health and can be considered as a preventive dietary supplement 45…”
mentioning
confidence: 99%